Perancangan Alat Penghitung Jumlah Pengunjung Konser Berbasis Mikrokontroler At89s51 - Eko Setia Budi (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2018)
In the current era of globalization, information technology advanced so quickly. The computer is the equipment created to facilitate the work of man, while achieving good progress in the manufacture of hardware and software. For that I am as a writer tries final project for the manufacture of tools called "Tool Counters Number of Visitors Microcontroller AT89S51-Based Concert". This tool serves as a counter number of the many visitors who come to a place. Details of existing information will be readily accepted as a provider of data recap many visitors automatically. For that I am here trying to practice and make this tool as a pilot and as inspirational. The design of this tool is very fit and have a good solution to help get the data without having to calculate and remember in mind manually.